Behavioural and cyto-genotoxic effects in adult rats and induced congenital anomalies to their embryos, exposed to environmentally relevant concentrations of phthalates - Edita Paulikaitė-Bivainė; Laurynas Orla; Justina Alčauskaitė; Evita Sėrikovaitė; Rokas Zalūba; Vaidotas Valskys; Valdas Šimčikas; Rokas Buišas; Rasa Aukštikalnienė; Violeta Žalgevičienė; Grita Skujienė (Ecotoxicology and Environmental Safety, 2025)
Phthalates are endocrine-disrupting chemicals widely used in everyday plastics and are increasingly recognised as dangerous to humans and ecosystems. In Lithuania, ineffective wastewater treatment has led to rising contamination with phthalates, particularly di(2-ethylhexyl) phthalate (DEHP) and dibutyl phthalate (DBP). As most prior studies used high short-term doses, this study focused on the effects of daily consumption of low environmentally relevant concentrations of DEHP and DBP on female rat physiology, reproduction, embryotoxicity and cyto-genotoxicity. Behavioural observations were included as an exploratory component to assess potential effects. Rats were given environmentally relevant phthalates with food for two months in three groups (200 µg/kg of DEHP, 100 µg/kg of DBP and a mix of both) and two groups for positive control (1000 µg/kg of DEHP and 500 µg/kg of DBP). The negative control group did not receive phthalates. Standard behavioural tests were conducted twice, general blood tests were carried out, and the rats were mated. On the 21st day of gestation, the pregnant rats were euthanised, bone marrow samples were taken for the micronucleus assay, and embryo viability and congenital anomalies were recorded. No significant behavioural or physiological changes were observed in adult rats. However, phthalates increased micronuclei in polychromatic erythrocytes and reduced the PCE/NCE ratio, indicating cyto-genotoxic effects. Long-term exposure to DEHP and DBP at environmentally relevant concentrations induced embryotoxic effects: embryo viability was compromised, with resorptions and morphological abnormalities. In summary, our results suggest that female exposure to phthalates, even in low environmental doses, has hidden cyto-genotoxic, reprotoxic and embryotoxic effects.